Trophic structure and functional diversity reveal pelagic-benthic coupling dynamic in the coastal ecosystem of Daya Bay, China. (June 2020) - Ying, Rui; Cao, Yiting; Yin, Fangmin; Guo, Jianlin; Huang, Jianrong; Wang, Yingyong; Zheng, Lianming; Wang, Junxing; Liang, Haoliang; Li, Zufu; Feng, Jianxiang
Highlights: Pelagic-benthic coupling related to trophic interaction was studied. Both pelagic and benthic communities were largely influenced by pelagic production. Seasonal variation of pelagic food caused trophic cascade and affected coupling. Trait-based functional diversity in Daya Bay was also influenced by seasonality. Abstract: Offshore marine areas have diverse habitats and food sources which lead to dynamic exchanges of nutrients and energy between different water layers. Coupling of energy pathways is related to both physical (e.g., sedimentation) and biological (e.g., predation) processes. However, due to the biological processes affected by human influences, the variability and dynamics of this coupling are not well quantified. Daya Bay, a subtropical semi-closed gulf affected by human activities, was studied to assess dynamics of pelagic-benthic coupling affected by trophical interaction. Stable isotope analyses of three main functional groups (pelagic fish, demersal fish, and benthic crustaceans) were conducted to assess trophic interactions, and trait-based functional indices were calculated to reveal the changes of community structure. The environmental variations, including chlorophyll a concentration, phytoplankton, and zooplankton abundance were monitored to explain the potential causes. The results showed that pelagic-benthic coupling effects were strong and seasonally dynamic in Daya Bay. Most nekton organisms were largely (>55%) fueled by pelagic production and exhibited high trophic overlap. In spring, when resources were limited, the proportion of the pelagic contribution to all the groups was highest, while greater trophic partitioning was observed. The trait-based functional diversity indices showed that the functional richness is extremely low in all seasons. However, the functional evenness and dispersion indices increased from winter to spring to summer. Our observation suggests that plankton abundance caused this seasonal pattern by controlling the strength of competitive interactions. Our study highlights the dynamic of pelagic-benthic coupling strength caused by trophic interaction across different environmental conditions of coastal ecosystems, this might provide important sighting on the coastal food web study and fishery management.